Using Ultrasonic Acoustics to Detect Cryptic Flying Squirrels: Effects of Season and Habitat Quality - Corinne A. Diggins; L. Michelle Gilley; Christine A. Kelly; W. Mark Ford (Wildlife Society Bulletin)
ABSTRACT New technologies allow for more efficient and effective monitoring of rare or elusive species. However, standardizing protocol to ensure high detection rates is important prior to widespread use of a new technique. The use of ultrasonic acoustic detectors to survey for flying squirrels (Glaucomys spp.) is a novel method that is more efficient than traditional methods. However, certain methodologies for this technique still need to be refined. During 2015, we conducted a seasonal and habitat quality study on the endangered Carolina northern flying squirrel (G. sabrinus coloratus) in western North Carolina, USA. Our seasonal study examined differences in probability of detection (POD) and latency to detection (LTD) at 30 high‐quality sites across 10 survey nights in spring, summer, and autumn. The habitat quality study focused on POD and LTD among 15 sites with varying habitat quality (5 High, 5 Medium, 5 Low) across 20 survey nights. We found POD similar between seasons, with POD 15–20% greater during spring. The LTD was comparable among seasons. We found that POD and LTD varied at sites with different habitat quality. The POD was similar between High and Medium sites (0.26 ± 0.04 SE and 0.29 ± 0.05, respectively), but greater than Low sites (0.02 ± 0.02). The LTD was not different among sites with differing habitat quality, although LTD at High sites was 2.7 and 4.5 times lower than Medium and Low sites, respectively. Trill calls, the most distinctive species‐specific call type produced by species of flying squirrels, was recorded at greater rates in spring versus other times of the year. Our results indicate flying squirrels can be surveyed during any season, although habitat quality needs to be considered when determining survey length. For Carolina northern flying squirrel, the optimal time to perform acoustic surveys is during the spring season for 6–10 survey nights at sites with high or medium habitat quality. © 2020 The Wildlife Society.